2019
DOI: 10.1007/s41669-019-0134-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Fulvestrant 500 mg in Endocrine Therapy-Naïve Postmenopausal Women with Hormone Receptor-Positive Advanced Breast Cancer in the UK

Abstract: IntroductionThe selective estrogen receptor degrader fulvestrant is approved for the first-line treatment of postmenopausal patients with hormone receptor-positive (HR+), locally advanced or metastatic breast cancer who have not received prior endocrine therapy. We evaluated the cost-effectiveness of fulvestrant versus comparator treatments in endocrine therapy-naïve patients with locally advanced or metastatic breast cancer.MethodsA three-health-state (progression free, progressed disease, and death) partitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Although endocrine therapy has reasonably lessened recurrence and mortality in breast cancer, acquired resistance to this treatment still limits the therapeutic efficiency, and new therapeutic strategies to overcome this resistance are in urgent need. Fulvestrant, a selective estrogen receptor degrader of endocrine therapy drugs, is approved as the first- or second-line treatment for postmenopausal female with ER-positive breast cancer who has no response to tamoxifen [ 28 30 ]. Clinical studies have demonstrated that fulvestrant dramatically improved the progression-free survival of patients [ 6 , 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although endocrine therapy has reasonably lessened recurrence and mortality in breast cancer, acquired resistance to this treatment still limits the therapeutic efficiency, and new therapeutic strategies to overcome this resistance are in urgent need. Fulvestrant, a selective estrogen receptor degrader of endocrine therapy drugs, is approved as the first- or second-line treatment for postmenopausal female with ER-positive breast cancer who has no response to tamoxifen [ 28 30 ]. Clinical studies have demonstrated that fulvestrant dramatically improved the progression-free survival of patients [ 6 , 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fulvestrant is a feasible and cost-effective treatment option in advanced breast cancer. 11 Although a variety of clinical trials in different treatment lines were available, the real-life data is limited. The real-life setting is very different from the clinical trials due to more unfit patients and more patients treated in the later lines due to physician preferences or reimbursement reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen articles estimated the cost effectiveness of therapies in the metastatic setting, including chemotherapy (n = 8), hormone receptor-targeted treatment (n = 2), HER2-targeted treatment (n = 2), and targeted (biologic) therapy (n = 6). [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Eight articles estimated the cost effectiveness of chemotherapeutic agents. 54,55,57,60,63,65,71,72 Four studies showed that the addition of palbociclib, a chemotherapy agent used for the treatment of hormone receptor-positive and HER2-negative breast cancer, had cost-effectiveness ratios that exceeded the US WTP threshold of $100,000 per QALY.…”
Section: Systemic Treatmentmentioning
confidence: 99%
“…55 Two articles estimated the cost effectiveness of fulvestrant, a hormonal treatment of advanced breast cancer, and each article found it to be cost effective in comparison with exemestane (aromatase inhibitor), letrozole (aromatase inhibitor), or tamoxifen at WTP thresholds in Sweden and the United Kingdom. 61,70 The cost effectiveness of HER2-targeted interventions for metastatic treatment exceeded the US WTP threshold of $100,000. 56,59 For example, the ICERs of trastuzumab emtansine were $183,828 per QALY compared with lapatinib plus capecitabine and $126,001 per QALY compared with capecitabine alone.…”
Section: Systemic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation